2018
DOI: 10.1016/j.ridd.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

How do maternal interaction style and joint attention relate to language development in infants with Down syndrome and typically developing infants?

Abstract: Reading's research outputs online How do maternal interaction style and joint attention relate to language development in infants with Down syndrome and typically developing infants?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Our findings in relation to the final predictive models for language development in children with ID on the second measurement occasion showed consistent relationships between the child's linguistic levels and the father's teaching scores, the father's educational level and the mother's anxiety levels. Our findings for father's teaching scores are consistent with the results of previous research that related parental behaviors of linguistic stimulation (e.g., comments, questions, explanations…) with child language development in typically developing children (Weisleder & Fernald, 2013;Schwab & Lew-Williams, 2016: Rowe et al, 2017Rowe & Snow, 2020) and in children with disabilities (Oakes et al, 2015;Seager et al, 2018). Contrary to what might be expected, a higher education level in the case of the fathers predicted lower linguistic development scores at T2, which we discuss above.…”
Section: Predictive Models For Child's Cognitive and Linguistic Devel...supporting
confidence: 91%
“…Our findings in relation to the final predictive models for language development in children with ID on the second measurement occasion showed consistent relationships between the child's linguistic levels and the father's teaching scores, the father's educational level and the mother's anxiety levels. Our findings for father's teaching scores are consistent with the results of previous research that related parental behaviors of linguistic stimulation (e.g., comments, questions, explanations…) with child language development in typically developing children (Weisleder & Fernald, 2013;Schwab & Lew-Williams, 2016: Rowe et al, 2017Rowe & Snow, 2020) and in children with disabilities (Oakes et al, 2015;Seager et al, 2018). Contrary to what might be expected, a higher education level in the case of the fathers predicted lower linguistic development scores at T2, which we discuss above.…”
Section: Predictive Models For Child's Cognitive and Linguistic Devel...supporting
confidence: 91%
“…However, the initial study of children diagnosed as having Down syndrome reveals the expected pattern of results on DREAM‐IT: Significantly lower scores on age‐appropriate Receptive language behaviours, and very little age‐appropriate behaviour reported for the expressive, play, and social domains. These data are compatible with other reports on children with Down syndrome in other languages and cultures (Seager et al., 2018; Yoder & Warren, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have found that receptive language is less affected than expressive language for children with Down syndrome; however, receptive skills are often below those of typically functioning children. The evidence on social communication skills such as joint attention for this group of children is mixed (Seager et al., 2018). For these reasons, the sample chosen for comparison was children with Down syndrome between ages 19 and 36 months, when some language skills typically emerge.…”
Section: Methodsmentioning
confidence: 99%
“…For this secondary analysis, we individually matched children with DS, ASD, and IDD from the larger study on chronological age and nonverbal cognitive abilities as measured by the MSEL (i.e., Mullen, 1995). Nonverbal cognitive abilities were estimated by combining the visual reception and fine motor domains (e.g., Barbaro & Dissanayake, 2017;Seager et al, 2018). Because the nonverbal cognitive T-scores ranged from below the floor to at or near the floor (see Table 1), we used nonverbal cognition raw scores for matching.…”
Section: Participantsmentioning
confidence: 99%